Study of Modular Multilevel Converter in AC/DC Hybrid Distribution Network. Issue 1 (August 2021) - Lei, Hou; Huizhuo, Ma; Yang, Liu; Yusen, Zhang; Yang, Su; Zhen, Sun
Abstract: The AC/DC hybrid power system plays an important role in the intelligent distribution network with the advantages of large power supply radius and capacity, low line cost and convenient distributed access. In this paper, a modular multilevel converter based on AC-DC side of AC/DC hybrid distribution network is exploited. An improved MPC sub-module capacitor voltage balance control method is proposed to reduce the calculation burden of MPC. The cost function is defined for phase currents, circulating currents, and sub-modules capacitor voltages. The weight factors of the cost function are eliminated, and the sub-module capacitor voltage control algorithm is improved to reduce the computational complexity of MPC. Not all cost functions for possible switching states combinations of MMC are calculated using improved method. The effectiveness of proposed improved method is evaluated based on 11 levels MMC system using Matlab/Simulink.